The economics and finance of cultural heritage how to make tourist attractions a regional economic resource - Pacelli, Vincenzo 1978-; Sica, Edgardo (Routledge cultural heritage and tourism series, 2021)
This book analyses the economic and financial profiles of heritage assets as tourist attractions. Offering both theoretical insights, methods, and global empirical examples, it considers how heritage assets can create economic and social value for a region. It offers an analysis of micro- and macroeconomic characteristics of heritage assets and their financial management. The importance of innovation in light of technological and market transformations is considered, as well as the sustainable management of heritage assets environmentally and in terms of sustainable tourism. The book delves into the financial assessment of heritage assets with a focus on evaluation models, the technique of project financing and wealth management in the art sector. These topics are illustrated with cases studies of heritage assets managed as tourist attractions to outline successful management strategies. The book draws on examples from a range of sites and locations across Italy, Spain, the United Kingdom, New Zealand, and the United States to show how heritage assets can be an economic stimulus for the development of local economies. The book will be of interest to academics and students at both undergraduate and postgraduate levels in the fields of tourism economics, cultural studies and environmental studies